Development of Website-Based Spinner Media Wheel of Names on The Material of Types of Improper Impurity And Procedures for Thaharah - Sofifah, Arinnatus; Burhanuddin, Hamam; Isroani, Farida (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by the problems that occurred at MTs Hidayatul Islam Tanjungharjo, namely in grade VII, which include the lack of school facilities and the lack of teacher innovation in using educational media. There are still many examples of worksheets and book packages in the educational process. To overcome these problems, the purpose of this study is to describe and understand the use of spinner teaching materials based on the Wheel of Names website, which includes the mystery of impurity and thaharah procedures, in the context of Fiqh education. The approach used is the ADDIE development model, which uses data collection techniques such as observation, interviews, and questionnaires, which include media, materials, teachers, and students. The results of the study indicate that the developed spinner media is quite feasible to use. Based on media analysis, 80% of students fall into the feasible category, 86.6% fall into the very feasible category from teachers, 96.6% fall into the very feasible category from teachers, and 95% fall into the very feasible category from students. Therefore, the spinner-based educational material based on the Wheel of Names is effective and innovative in improving the fiqh learning process. This media not only inspires but also facilitates students' interactive understanding of the material. Based on validation from several sources, this material is quite beneficial in the educational process at school.